Investigating Project and Asset Management Integration Ensuring Reliable Handovers in Production Projects - INGVARSSON, DANIEL; JOHANSSON, FILIP (My University, 2025)
Efficient management of resources, ensuring reliable operations, has become increasingly important for Swedish Match. A critical aspect of achieving this is the transition from project development to implementation. Challenges often arise during the handover due to unclear processes, missing information, and inadequate planning, leading to inefficiencies. This thesis analyses project structures and responsibilities. Identifying problem areas in the different project phases, the thesis aims to find ways to ensure operational reliability and effective data management. The purpose is to find critical areas in the project process that hinder production and operation & maintenance from managing the production equipment over its lifecycle. The thesis addresses key challenges in the handover of production projects concerning project management and asset management integration and investigates solutions that can be implemented. The methodology includes a literature study, a case study, and a process study. The case study involves analyses of documented processes and structures, alongside interviews. The process study supports the findings by following an ongoing project and gathering information through documentation analysis and observations. The analyses identified several areas of improvement and challenges concerning project handover. These include the necessity of clear roles and responsibilities. Setting higher standards by the steering committee, overseeing prioritization, and continuously reviewing ongoing and previous projects. Involvement of the receiving organizations in project orders was identified as important, together with detailed handover requirements to reach satisfaction from both parties. Establishing a standard for project documentation was also identified as necessary, alongside ensuring effective and reliable communication channels.
Keywords: Project management; Asset management; Project handover; Project structure